If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x * 2x + 2x + -12 = 0 Reorder the terms for easier multiplication: 2 * 2x * x + 2x + -12 = 0 Multiply 2 * 2 4x * x + 2x + -12 = 0 Multiply x * x 4x2 + 2x + -12 = 0 Reorder the terms: -12 + 2x + 4x2 = 0 Solving -12 + 2x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-6 + x + 2x2) = 0 Factor a trinomial. 2((-2 + -1x)(3 + -2x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {-2, 1.5}
| -6(v+3)+3v+6=6v+8 | | 54x^2+48x+11=0 | | 315/x=4/16 | | .5x=1.56 | | 6+10x=-94 | | 2[7-6(1-n)]+9=-32+6[6(n+1)-3n] | | 2/7b=1/7 | | 0=2y-3 | | 2sin^2(x)-sin(x)-1=0 | | 4n+16=56 | | X^4+6x-108=0 | | 1/3y≥5 | | .3x-5.04=-6.3 | | f(f(x))=25x+9 | | H(t)=-16t^2+72t+5 | | 4/3(pi)10^3 | | 5y=0-10 | | x^2-10x-25=21-25 | | -38=5(2y-1) | | x+0.5=3.2 | | 0-10=5y | | -6/5x=-7 | | 1-cos(6x)=3cos(2x) | | 1/6t=4 | | Y=sin(4x) | | (-2/3)x^2-5 | | 5x^2+13-6=0 | | 10h+5=85 | | 19z-6(4z-1)= | | 20x^2+5.2x-0.5=0 | | 0=8-2y | | 6=2.5(w-2) |